Influência da microgeração fotovoltaica no perfil de demanda e seus impactos na geração de harmônicos na rede - PARIJÓS JÚNIOR, Ivan Ruy de (Universidade Federal do Pará, 2025)
This study addresses the integration of photovoltaic generation into the electrical grid, emphasizing the necessity to consider changes in the load profile of consumer units and the presence of harmonic components in the grid current, originating from loads with nonlinear characteristics and photovoltaic inverters. Various percentages of inverter loading were considered in the study to evaluate their impact on grid operation due to varying levels of harmonic components. The research comprises an experimental phase, a phase dedicated to developing models of inverter output currents, and a simulation phase. In the experimental phase, data on the output currents of three photovoltaic inverters were collected. These data were then utilized in the development of models of inverter output currents for theoretical analyses, evaluating factors influencing the power quality of the grid. Subsequently, these models were applied in the simulation phase. The grids evaluated in the simulation phase include a standard IEEE system and a real isolated grid, located in the Northern region of Brazil. Comparative assessments of network, hosting capacity were conducted using two different strategies. The first strategy employed conventional power flow analysis, while the second strategy applied the developed models. It is observed that the operation of different inverters within the same grid may contribute to harmonic attenuation. Furthermore, it is highlighted that the presence of grid-connected photovoltaic systems, operating in conjunction with loads, results in an apparent increase in harmonic current content in the grid, whereas, in reality, there is a reduction in the circulating fundamental component. The obtained results indicate that conventional power flow studies may underestimate the intensity of circulating currents in the grid by neglecting the presence of harmonic components. This study innovates by assessing the circulation of harmonic components in the grid due to the combined operation of photovoltaic generation and load, considering various inverter loading scenarios and the effects of consumer electrical current, including the phase of harmonic components.